2020
DOI: 10.1039/c9fo02460c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semolina pudding prepared fromstarch branching enzyme IIaandbmutant wheat on glycaemic responsein vitroandin vivo: a randomised controlled pilot study

Abstract: Refined starchy foods are usually rapidly digested, leading to poor glycaemic control, but not all starchy foods are the same. Complex carbohydrates like resistant starch (RS) have been shown to reduce the metabolic risk factors for chronic diseases such as hyperglycaemia and overweight. The aim of the project was to develop a semolina-based food made from a starch branching enzyme II (sbeIIa/b-AB) durum wheat mutant with a high RS content and to measure its glycaemic index using a double-blind randomised pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Hoebler et al [ 55 ] showed that bread rich in amylose had a lower starch degradation compared to control bread. Corrado et al [ 56 ] reported that the starch amylolysis rate and extent were lower for SBEIIa/b-AB compared to those of the control. In rice, the starch digestion rate (k) decreased in flour blend with an increased amount of the HA maize starch [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoebler et al [ 55 ] showed that bread rich in amylose had a lower starch degradation compared to control bread. Corrado et al [ 56 ] reported that the starch amylolysis rate and extent were lower for SBEIIa/b-AB compared to those of the control. In rice, the starch digestion rate (k) decreased in flour blend with an increased amount of the HA maize starch [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The development and commercialisation of high amylose wheat-based products will allow new products with higher fibre and better sensory acceptability than current wholemeal and wholegrain wheat products designed to increase fibre. Recently, Corrado [ 56 ] reported a semolina pudding made from a SBEIIa durum wheat mutant with resistant starch content of ~5%, digested more slowly and to a lesser extent by in vitro test than wild type control. However, they found no difference in the foods GI.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various starch biosynthetic enzymes, it is clear that reduction in the level of amylopectin biosynthesis enzymes, BEIIb and/or SSIIIa, leads to high amylose content (Fujita 2014;Wang et al 2017). Importantly, suppression of multiple BE isozymes allows the accumulation of amylose and RS to high levels in maize (Li et al 2008), wheat (Regina et al 2006;Corrado et al 2020), barley (Regina et al 2010;Carcio et al 2012), and rice (described later). In a rat feeding trial, intake of RS improved gastrointestinal health (Regina et al 2006;Zhu et al 2012), and prevented sudden increase in blood glucose levels (Zhu et al 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Among the various starch biosynthetic enzymes, it is clear that reduction in the level of amylopectin biosynthesis enzymes, BEIIb and/or SSIIIa, leads to high amylose content (Fujita 2014;Wang et al 2017). Importantly, suppression of multiple BE isozymes allows the accumulation of amylose and RS to high levels in maize (Li et al 2008), wheat (Regina et al 2006;Corrado et al 2020), barley (Regina et al 2010;Carciofi et al 2012), and rice (described later). In a rat feeding trial, intake of RS improved gastrointestinal health (Regina et al 2006;Zhu et al 2012), and prevented sudden increase in blood glucose levels (Zhu et al 2012).…”
Section: Generation Of Non-transgenic Rice Lines Deficient In Bei and Beiibmentioning
confidence: 99%